Selinexor’s Immunomodulatory Impact in Advancing Multiple Myeloma Treatment - Tasbihi, Kereshmeh; Bruns, Heiko (Cells, 2025)
Despite the major advancements in the repertoire for multiple myeloma (MM) treatment, this disease remains a chronically progressive plasma cell malignancy. Drug resistance and high relapse rates complicate the extended treatment strategies. However, the tumor microenvironment (TME) in MM is decisive for the success of a therapy or relapse. Aiming to improve the outcome of relapsed and refractory MM patients, Selinexor has entered the drug arsenal of myeloma therapy through the implementation of a novel therapeutic approach by selectively inhibiting the nuclear export receptor Exportin-1 (XPO1). Selinexor leads to the inactivation of cancer-related proteins and induces apoptosis by disrupting the nucleocytoplasmic flow in myeloma cells. While this drug is selectively cytotoxic to neoplastic cells, Selinexor’s immunomodulatory impact on the TME is currently being investigated. The aim of this review was to elucidate Selinexor’s capacity to influence the cell interaction network of the TME from an immunological perspective. Deciphering the complex interplay of highly plastic immune cells provides a contribution to the molecular–biological exploration of disease initiation and progression in MM. Unraveling the novel therapeutic targets of the immunological TME and evaluating the advanced immunotherapeutic regimens implementing Selinexor will shape the future directions of immune-oncotherapy in MM.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Exportin-1; immunotherapy; multiple myeloma; nuclear export; Selinexor; tumor microenvironment; XPO1; XPOVIO